Magnetite–Sulfuric Acid Magnetic Nanoparticles: Preparation and Application in Synthesis of Mono-, Bis-, and Tris-14H-Dibenzo[a,j]xanthen-14-ylarenes under Solvent-Free Conditions - Karimi, Ali Reza; Dalirnasab, Zeinab; Karimi, Marzie (Synthesis, 2014)
Novel magnetite–sulfuric acid (Fe3O4·SO3H) magnetic nanoparticles were prepared by the direct reaction of chlorosulfonic acid with magnetite nanoparticles, and characterized by IR spectroscopy, thermogravimetric analysis, X-ray diffraction, and scanning electron microscopy. The catalytic activity of the Fe3O4·SO3H nanoparticles in the reaction of 2-naphthol with aryl mono-, di- and trialdehydes was examined, and these catalysts were shown to exhibit remarkable catalytic performance in the solvent-free synthesis of mono-, bis-, and tris-14H-dibenzo[a,j]xanthen-14-ylarenes. The catalyst retained its activity for several cycles.
Keywords: polycycles; heterocycles; catalysts; heterogeneous catalysis; condensation; cyclizations